Association of Systolic Blood Pressure and Cerebral Collateral Flow in Acute Ischemic Stroke by Stroke Subtype - Sim, Jae Eun; Chung, Jong-Won; Seo, Woo-Keun; Bang, Oh Young; Kim, Gyeong-Moon (Frontiers in Neurology, 2022)
Background and purpose: Collateral flow in acute ischemic stroke is known as a predictor of treatment outcome and long-term prognosis. However, factors determining the initial collateral flow remain unclear. We investigated factors related to collateral flow in patients with acute ischemic stroke caused by large vessel occlusion (AIS-LVO) and further analyzed the results according to stroke etiology. Methods: This was a retrospective study using prospective stroke registry data from a single university hospital from October 2014 to May 2021. AIS-LVO with middle cerebral artery M1 occlusion identified by pre-treatment multiphasic computed tomography angiography were included. Collateral flow score was graded on a six-point ordinal scale according to pial arterial filling. Results: A total of 74 patients (cardioembolism [CE]: 57; large artery atherosclerosis [LAA]: 17) was included. The mean age of all patients was 72.2 ± 11.7 years, and 37.8 % (n = 28) were males. Multivariate regression analysis showed that initial SBP (odds ratio [OR]: 0.994; 95% confidence interval [CI]: 0.990-0.998; p = 0.002) and stroke etiology (OR: 0.718; 95% CI: 0.548-0.940; p = 0.019) were independent factors of the collateral flow grade. Collateral flow grade was independently associated with initial SBP in the CE group (OR: 0.993; 95% CI: 0.989-0.998; p = 0.004) but not in the LAA group (OR: 0.992; 95% CI: 0.980-1.004; p = 0.218). Initial SBP was significantly correlated with NIHSS score in the CE group but not in the LAA group (r2 =0.091, p = 0.023; r2 = 0.043, p = 0.426, respectively). Conclusions: Elevated initial SBP was associated with poor cerebral collateral flow and more severe symptoms in the CE group, but not in the LAA group in patients with AIS-LVO. These findings suggest differential effects of initial SBP elevation on collateral flow by stroke subtypes.